Instruments used to assess oral health-related quality of life of children - Aljohani, Hanan Raja; Alshammari, Khalid Mubarak; Shaikh, Ahmed Mohammed; Alotaibi, Turki Nasser; Alshehri, Abdullah Ali; Alsaikhan, Abdullah Ali; Almalky, Alanoud Meteb; Zahran, Majed Mohammad; Bushnag, Anaan Ibrahim; Alyami, Fatimah Ismail; Alanzi, Sarah Khalid (International Journal Of Community Medicine And Public Health, 2022)
To evaluate oral health-related quality of life (OHRQoL) in children, both the clinical indices and parenteral reporting can be used to achieve this effect. The present review provides evidence regarding the currently available instruments to assess the OHRQoL in children. Many instruments were reported, and some were designated for preschoolers. In contrast, others for schoolchildren and adolescents, and some researchers reported that some tools could be used to assess OHRQoL in different age groups. Moreover, some tools can also be used to assess the OHRQoL of children based on their parent's perspectives. The POQL, FIS, PedsQL™ oral health scale™, and P-CPQ are the only modalities that can effectively assess OHRQoL in all adolescents and all childhood cycles. Moreover, the OHRQoL hypodontia questionnaire, MIQ, IFAQ, DFTO, CPQ11-14, CPQ8-10, child-OIDP, child-OHIP, and child-DPQ are the currently available tools that can be used to assess OHRQoL in adolescents and schoolchildren. Regarding the assessment of OHRQoL in preschoolers, it has been shown that the only available tools for this context include the SOHO-5, OH-ECQOL, Michigan-OHRQoL, ECOHIS, and DDQ questionnaires.